2012
DOI: 10.5293/ijfms.2012.5.4.161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blade Row Distance on Performance and Flow Condition of Contra-Rotating Small-Sized Axial Fan

Abstract: Small-sized axial fans are used as air coolers for electric equipment. There is a strong demand for higher power of fans according to the increase of quantity of heat from electric devices. Therefore, higher rotational speed design is conducted, although, it causes the deterioration of the efficiency and the increase of noise. Then, the adoption of contrarotating rotors for small-sized fans is proposed for the improvement of the performance. In the case of contra-rotating rotors, blade row distance between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…They eventually observe that the blockage effect of the rear rotor on the flow field close to the front rotor blades trailing edges seems stronger than the effects of the front rotor wake on the rear rotor. The effect of the axial distance between the counter-rotating rotors of an axial-flow fan is studied by Shigemitsu et al [19]. They conclude that the influence of this distance on static pressure rise is stronger at partial flow rate than at design flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…They eventually observe that the blockage effect of the rear rotor on the flow field close to the front rotor blades trailing edges seems stronger than the effects of the front rotor wake on the rear rotor. The effect of the axial distance between the counter-rotating rotors of an axial-flow fan is studied by Shigemitsu et al [19]. They conclude that the influence of this distance on static pressure rise is stronger at partial flow rate than at design flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Counter-rotating axial turbomachines such as propellers, axial-flow pumps and low-speed fans are used in various industrial domains [1][2][3][4][5][6][7]. In a counter-rotating stage (CRS), the front rotor (FR) and the rear rotor (RR) rotate in opposite directions (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the axial distance between the counterrotating rotors of an axial-flow fan is studied by Shigemitsu et al [5]. They conclude that the influence of this distance on static pressure rise is stronger at partial flow rate than at design flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [9] found it was meaningless to lengthen the axial gap when it was over 80% of the chord and the optimal axial gap was about 70%. Shigemitsu et al [10] discussed the influences on the performance and the noise of axial distance. They showed the interaction between the front and the rear rotors.…”
Section: Introductionmentioning
confidence: 99%